1993
DOI: 10.1002/bip.360330905
|View full text |Cite
|
Sign up to set email alerts
|

Stretching and overstretching of DNA in pulsed field gel electrophoresis. I. A quantitative study from the steady state birefringence decay

Abstract: SYNOPSISUsing a sensitive birefringence instrument, the birefringence arising from the orientation of the DNA chain during electrophoretic transport has been recorded. This birefringence is shown to proceed both from the alignment (stretching) of the molecule in the direction of the electric field and from the extension of the length of its primitive path (overstretching) . The contribution of these two processes can be separated in the decay of the birefringence after the end of the application of the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 24 publications
4
52
0
Order By: Relevance
“…The study by Weill and co-workers [21] has shown that the field strength and DNA size dependence of the tube orientation is in good agreement with the reptation theory, and Stube can therefore be expected to follow the predicted decrease as the pores become smaller in denser gels. This proposal has not been tested directly by measurements of Stub, at different gel concentrations, and may seem to be contradicted by the observation that the total DNA orientation, S , goes through a maximum…”
Section: Denser Gel: Less Frequent But Equally Long Stepsmentioning
confidence: 65%
See 1 more Smart Citation
“…The study by Weill and co-workers [21] has shown that the field strength and DNA size dependence of the tube orientation is in good agreement with the reptation theory, and Stube can therefore be expected to follow the predicted decrease as the pores become smaller in denser gels. This proposal has not been tested directly by measurements of Stub, at different gel concentrations, and may seem to be contradicted by the observation that the total DNA orientation, S , goes through a maximum…”
Section: Denser Gel: Less Frequent But Equally Long Stepsmentioning
confidence: 65%
“…3) [20,21,261. In this kind of experiment the molecules are first allowed to reach equilibrium in the gel by turning off the field for tens of minutes [26].…”
Section: Spectroscopic Ensemble Averages Of L and Tmentioning
confidence: 99%
“…(4), i.e., For that purpose, one defines the ratio (33) where F(a/l) = 1-3 a/NLang-'(all) where Lang-' is the inverse Langevin function. [12] for dsDNA in agarose gels [13]. The time z', is an important dynamical parameter when devising pulse trains for pulsed field gel electrophoresis.…”
Section: Overstretching Of the Chainmentioning
confidence: 99%
“…Following the procedure described by Mayer et al [12], the contribution of overstretching to birefringence, as taken from the second term in the bracket of Eq. (4), i.e., For that purpose, one defines the ratio (33) where F(a/l) = 1-3 a/NLang-'(all) where Lang-' is the inverse Langevin function.…”
Section: Overstretching Of the Chainmentioning
confidence: 99%
“…
Influence of optical probing with YOYO on the electrophoretic behavior of the DNA molecule
Department ofThe influence of the fluorescent dye YOYO (1,[1][2][3][4]4,8,8,-tetramethylChahers University of
4,8-diazaundecamethylene)bis[4-[[3-methyl-benzo-1,3-oxazol-2-yl]methylidene]-Goteborg, Sweden 1,4-dihydroquinolinium] tetraiodide) on the electrophoretic behavior of the DNA molecule was investigated. This is important when using YOYO as a probe in capillary electrophoresis or in fluorescence microscopy studies of DNA with the purpose of studying the migration mechanism of DNA on the molecular level.
…”
mentioning
confidence: 99%